IOC Consensus Statement: Dietary Supplements and the High-Performance Athlete - Maughan, Ronald J; Burke, Louise M; Dvorak, Jiri; Larson-Meyer, D Enette; Peeling, Peter; Phillips, Stuart M; Rawson, Eric S; Walsh, Neil P; Garthe, Ina; Geyer, Hans; Meeusen, Romain; van Loon, Luc; et al. (International journal of sport nutrition and exercise metabolism, 2018)
Nutrition usually makes a small but potentially valuable contribution to successful performance in elite athletes, and dietary supplements can make a minor contribution to this nutrition program. Nonetheless, supplement use is widespread at all levels of sport. Products described as supplements target different issues, including the management of micronutrient deficiencies, supply of convenient forms of energy and macronutrients, and provision of direct benefits to performance or indirect benefits such as supporting intense training regimens. The appropriate use of some supplements can offer benefits to the athlete, but others may be harmful to the athlete's health, performance, and/or livelihood and reputation if an anti-doping rule violation results. A complete nutritional assessment should be undertaken before decisions regarding supplement use are made. Supplements claiming to directly or indirectly enhance performance are typically the largest group of products marketed to athletes, but only a few (including caffeine, creatine, specific buffering agents and nitrate) have good evidence of benefits. However, responses are affected by the scenario of use and may vary widely between individuals because of factors that include genetics, the microbiome, and habitual diet. Supplements intended to enhance performance should be thoroughly trialed in training or simulated competition before implementation in competition. Inadvertent ingestion of substances prohibited under the anti-doping codes that govern elite sport is a known risk of taking some supplements. Protection of the athlete's health and awareness of the potential for harm must be paramount, and expert professional opinion and assistance is strongly advised before embarking on supplement use.